Analysis of Occupational Health and Safety Risks In The Manufacturing Industry With The Hirarc Method at PT. X - Hosiah, Hosiah; Zakkiy Fasya, Abdul Hakim (Devotion : Journal of Research and Community Service, 2022)
Batching plant is better known as a concrete processing plant, all of the tools are specially designed to mix or combine materials to form concrete. Sources of potential hazards that exist in the work environment are caused by the batching plant machine, the use of heavy equipment transportation, and office areas. The purpose of this study is to analyze the potential hazards that could occur in the work environment to carry out control or prevention at PT. X. This research was a quantitative descriptive study, to analyze occupational health and safety risks using the HIRARC method. The number of respondents was 4 people including management, SHE (Safety Health and Environment), and 2 operators of PT. X's batching plant. The variables of this research are risk identification, risk assessment, and risk control. The instruments used were observation, document review, and interviews using risk analysis guidelines with the HIRARC method. The results of this study indicate that the potential risks that could occur in the work environment include 14 work processes that could cause as many as 31 hazards with 42 potential hazards. The results of the research findings of hazard were grouped into 4 risk ratings, at a very high-risk rating there were 0 risks, at a high-risk rating there were 8 risks, at a medium risk rating there were 27 risks, and at a low-risk rating, there were 7 risks. Based on the result, it could be stated that this study, is the implementation of risk analysis using the HIRARC method as an effort to prevent potential hazards that could occur in the work environment at PT. X can be controlled by installing OHS signs, training workers, machine maintenance, maintaining the workplace/supervision at work, using equipment and working methods in safe conditions, providing PPE (masks, gloves, catelpak /vests, helmets, earmuffs/earplugs), involve competent workers to make a risk analysis with HIRARC